PENGEMBANGAN KEMAMPUAN MEMBACA PERMULAAN ANAK MELALUI MEDIA MEMBACA CANTOL ROUDHOH USIA 5-6 TAHUN - Beru Menye Puspitasari; Isti Rusdiyani; Ratih Kusumawardani (Early Childhood Teacher Education Department UNIVERSITAS SULTAN AGENG TIRTAYASA, 2020)
The purpose of this study was to determine 1) the reading ability of children aged 5-6 years at TKIT Gugus Bintang 165 Tangerang. 2) the learning process uses cantol roudhoh picture card media to develop reading skills of children aged 5-6 years at TKIT Gugus Bintang 165 Tangerang. 3) the process of evaluating the ability to read children aged 5-6 years through the media card cantol roudhoh at TKIT Gugus Bintang 165 Tangerang. This research was conducted in May 2016. With the research location in TKIT Gugus Bintang 165 Tangerang Banten. The subjects of this study were children aged 5-6 years, totaling 15 children. The method used in this study is a qualitative research method. Data collection techniques through observation, field notes, interviews and documentation. Data analysis using data reduction, data presentation and conclusions. Data validation is done by extending the observation, increasing research persistence, triangulation, checking members. Based on data analysis, it states that the development of reading skills of children aged 5-6 years at TKIT Gugus Bintang 165 Tangerang Banten develops well. This can be observed from 8 indicators that researchers use as a reference. Can also be observed in the learning process at school, the development of children's reading skills including: there are children who are able to read their own names completely and correctly, children are able to distinguish vowels and consonants, children are able to connect images with writing, and children able to group images that have the same prefix sound.